PD‐L1 overexpression correlates with JAK2‐V617F mutational burden and is associated with 9p uniparental disomy in myeloproliferative neoplasms. Issue 4 (21st January 2022) - Milosevic Feenstra, Jelena D.; Jäger, Roland; Schischlik, Fiorella; Ivanov, Daniel; Eisenwort, Gregor; Rumi, Elisa; Schuster, Michael; Gisslinger, Bettina; Machherndl‐Spandl, Sigrid; Bettelheim, Peter; Krauth, Maria‐Theresa; Keil, Felix; et al.
Abstract: Myeloproliferative neoplasms (MPN) are chronic stem cell disorders characterized by enhanced proliferation of myeloid cells, immune deregulation, and drug resistance. JAK2 somatic mutations drive the disease in 50–60% and CALR mutations in 25–30% of cases. Published data suggest that JAK2 ‐V617F‐mutated MPN cells express the resistance‐related checkpoint PD‐L1. By applying RNA‐sequencing on granulocytes of 113 MPN patients, we demonstrate that PD‐L1 expression is highest among polycythemia vera patients and that PD‐L1 expression correlates with JAK2 ‐V617F mutational burden ( R  = 0.52; p  < .0001). Single nucleotide polymorphism (SNP) arrays showed that chromosome 9p uniparental disomy (UPD) covers both PD‐L1 and JAK2 in all MPN patients examined. MPN cells in JAK2 ‐V617F‐positive patients expressed higher levels of PD‐L1 if 9p UPD was present compared to when it was absent ( p  < .0001). Moreover, haplotype‐based association analyses provided evidence for germline genetic factors at PD‐L1 locus contributing to MPN susceptibility independently of the previously described GGCC risk haplotype. We also found that PD‐L1 is highly expressed on putative CD34 + CD38 − disease‐initiating neoplastic stem cells (NSC) in both JAK2 and CALR ‐mutated MPN. PD‐L1 overexpression decreased upon exposure to JAK2 blockers and BRD4‐targeting agents, suggesting a role for JAK2‐STAT5‐signaling and BRD4 in PD‐L1 expression. Whether targeting of PD‐L1 can overcome NSC resistance in MPN remains to be elucidated in forthcoming studies.